Evaluasi program baca al-Qur’an dan shalat Dhuha di SMK Muhammadiyah Gamping Sleman - Nizar Ibnu Albar; Syamsudin Syamsudin (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
The congregational Quran reading and Dhuha prayer program in schools require comprehensive evaluation to understand the effectiveness, sustainability, and impact of the program. This research aims to evaluate the implementation of the Quran reading and Dhuha prayer program at SMK Muhammadiyah Sleman by analyzing contextual, input, process, and product aspects using the CIPP evaluation model. An evaluative method is employed as the methodological foundation to collect essential data for assessing contextual, input, process, and product aspects of a program. The research was conducted at SMK Muhammadiyah Gamping Sleman, involving the school principal, ISMUBA teachers, and SMK students as research subjects. Data were gathered through observation, interviews, and documentation. The research findings indicate that: (1) concerning the implementation context of the Quran reading and Dhuha prayer program, some students face difficulties in reading the Quran and developing Islamic character through worship practices. (2) Input aspects, including teacher preparation and facilities such as classrooms and prayer rooms, were found to be in very good condition. (3) The implementation process of Quran reading and Dhuha prayer involves methods and assessments that allow students to take turns reading using guidebooks and recording attendance. (4) The results of the Quran reading program include an improvement in Quran reading abilities, while the impact of the congregational Dhuha prayer program outside of school is still not measurable by the school.